ENERGY POTENTIAL STUDY OF BANDUNG THEMATIC PARK BIOMASS WASTE BASED ON LITERATURE OF THE EFFECT OF TEMPERATURE AND HEATING RATE VARIATION ON BIOMASS WASTE PYROLYSIS - Maziyyah Munawaroh, Salma
Solid waste is a major problem in the management of public facilities, including biomass waste in Bandung Thematic Park. Biomass waste has the potential for energy to be generated. In addition, the availability of this renewable energy is unlimited and can be used continuously. So we need an efficient and environmentally friendly method to use it. One method that can be used is the pyrolysis process to obtain bio-oil products. The source of biomass energy has several advantages, including a renewable energy source so that it can provide a sustainable energy source (sustainable). The depletion of petroleum reserves and the increasing human population are very contradictory to the energy requirements for human survival and economic and social activities. Bio-oil is an alternative fuel to replace petroleum which is renewable (renewable fuel) derived from biomass.